Molluscum contagiosum and dental caries: A pertinent combination - Dixit S; Chaudhary M; Singh A (Wolters Kluwer Medknow Publications, 2009)
Background: In recent decades, there has been a tremendous surge of interest in issues related to child health. The present study was carried out to reveal the DMFT/deft status of children in the age group of 1-12 years, residing in orphanages from Pune, India. Aims and Objectives: To explore the DMFT/deft status in various orphanages from Pune (India). To find out differences, if any, between the DMFT/deft status in orphanages from Pune, India, and the general population of children below 12 years of age in Maharashtra state, India as well as all over India. Results: DMFT/deft of the orphanages was found to be 2.58 in the age group 1-5 years and 2.5 in the age group 6-12 years with caries prevalence in 70.27% of the children. An incidental finding of Molluscum contagiosum was observed in a significant percentage of children. The total percentage of children afflicted by Molluscum contagiosum was found to be 24.32%. Conclusion: The higher incidence of Molluscum contagiosum in children residing in orphanages as compared to the normal population of the same age group was reflected in the higher incidence of DMFT/deft in orphanages as compared to the normal population.